2015
DOI: 10.1063/1.4922446
|View full text |Cite
|
Sign up to set email alerts
|

Resistance controllability and variability improvement in a TaOx-based resistive memory for multilevel storage application

Abstract: In order to obtain reliable multilevel cell (MLC) characteristics, resistance controllability between the different resistance levels is required especially in resistive random access memory (RRAM), which is prone to resistance variability mainly due to its intrinsic random nature of defect generation and filament formation. In this study, we have thoroughly investigated the multilevel resistance variability in a TaOx-based nanoscale (<30 nm) RRAM operated in MLC mode. It is found that the resistance va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 18 publications
(30 reference statements)
2
51
0
Order By: Relevance
“…It has been shown in the literature 3,4 and is shown in this work that atomic doping can improve both requirements. Evolution of a conductive filament and its rupture and restoration have been studied by various analytical and numerical models [10][11][12][13][14] We have previously reported the properties of Ovac in the λ phase of Ta2O5 crystal 15 and in the amorphous Ta2O5 network 16 through sX density functional simulations.…”
Section: The Reduction In Hrs Current Withmentioning
confidence: 52%
See 4 more Smart Citations
“…It has been shown in the literature 3,4 and is shown in this work that atomic doping can improve both requirements. Evolution of a conductive filament and its rupture and restoration have been studied by various analytical and numerical models [10][11][12][13][14] We have previously reported the properties of Ovac in the λ phase of Ta2O5 crystal 15 and in the amorphous Ta2O5 network 16 through sX density functional simulations.…”
Section: The Reduction In Hrs Current Withmentioning
confidence: 52%
“…This effect has been observed in sputtered TaOx films by controlling the oxygen partial pressure during sputtering 3 . It was concluded that the variability of the conductive filament resistance depends on both the filament diameter and the oxygen vacancy density in the filament.…”
Section: The Reduction In Hrs Current Withmentioning
confidence: 82%
See 3 more Smart Citations